Effect of Electron Beam Treatment in Air on Surface Properties of Ultra-High-Molecular-Weight Polyethylene - Grubova I. Yu. Irina Yurievna; Surmeneva M. A. Maria Alexandrovna; Shugurov V. V. Vladimir Viktorovich; Koval N. N. Nikolay Nikolaevich; Selezneva I. I. Irina Ivanovna; Lebedev S. M. Sergey Mikhailovich; Surmenev R. A. Roman Anatolievich (2016, 2016)
Title screen